2002
DOI: 10.1007/s003440010049
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Signaling in Plant Responses to Gravity and Touch

Abstract: Touch and gravity are two of the many stimuli that plants must integrate to generate an appropriate growth response. Due to the mechanical nature of both of these signals, shared signal transduction elements could well form the basis of the cross-talk between these two sensory systems. However, touch stimulation must elicit signaling events across the plasma membrane whereas gravity sensing is thought to represent transformation of an internal force, amyloplast sedimentation, to signal transduction events. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
99
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 0 publications
4
99
0
Order By: Relevance
“…Mechanical stimuli such as wind, rain, and obstacles in the soil trigger changes in growth patterns (Braam and Davis, 1990;. Gravitropic and mechanical stimulation in the root are interactive processes, mutually influencing differential growth (Mullen et al, 2000;Fasano et al, 2002;. The mechanisms of sensing and signal transduction for either stimulus are not well understood, but it has been shown that the transcript levels of specific genes are regulated early during signal transduction after either stimulus Braam and Davis, 1990).…”
mentioning
confidence: 99%
“…Mechanical stimuli such as wind, rain, and obstacles in the soil trigger changes in growth patterns (Braam and Davis, 1990;. Gravitropic and mechanical stimulation in the root are interactive processes, mutually influencing differential growth (Mullen et al, 2000;Fasano et al, 2002;. The mechanisms of sensing and signal transduction for either stimulus are not well understood, but it has been shown that the transcript levels of specific genes are regulated early during signal transduction after either stimulus Braam and Davis, 1990).…”
mentioning
confidence: 99%
“…Chemical stimuli induce changes of electrical potential, which in turn stimulate growth of etiolated seedlings and affect nutation and phototropic movements (Spalding and Cosgrove 1993). Touch and gravitation are stimuli, which affect growth of Arabidopsis seedlings, and APs, besides other candidates, are recognized as factors mediating between stimulus and reaction (Fasano 2002).…”
Section: Physiological Role Of Electrical Activity In Plantsmentioning
confidence: 99%
“…Unfortunately, it is not trivial to monitor changes in intracellular calcium between different stores. Investigators have had to resort to very indirect methods to gauge the impact of Ca 2+ on gravitropism such as application of Ca 2+ channel blockers or Ca 2+ chelators or by removing/altering the function of certain calcium regulatory proteins such as calmodilin-like proteins (for review see Fasano et al, 2002). Recently, however, Plieth and Trewavas (2002) used a luminescent Ca 2+ reporter aequorin to look at transient increases in [Ca 2+ ] cyt .…”
Section: Center Of Gravitymentioning
confidence: 99%
“…Interestingly, other mechanical stimulations don't have the same effect on [Ca 2+ ] cyt spiking (Plieth and Trewavas, 2002). Future experiments should include using this biosensor for calcium in conjunction with amyloplast mutants to see whether a link can truly be drawn between the sedimentation of starch molecules and the transient changes in [Ca 2+ ] cyt (Plieth and Trewavas, 2002;Fasano et al, 2002). Inositol-1,4,5-triphosphate (IP3) is another potential second messenger.…”
Section: Center Of Gravitymentioning
confidence: 99%